THE RELATIONSHIP OF FAMILY SUPPORT AND KNOWLEDGE WITH MENARCHE READINESS - Budiarti, Astrida; Clarrita, Mellienia Bunga; Chabibah, Nur; Ernawati, Dwi (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
Menarche is the first menstruation which can make some young women feel afraid and anxious. There are still teenagers who think menstrual bleeding is scary and painful. Family support in preparing teenagers for menarche is also still lacking. The aim of this research is to analyze the relationship between knowledge and family support and readiness to menarche. This research design uses correlation analytics with a cross sectional approach. Population is female teenagers in grades V and VI at SD Al Kautsar Surabaya. The sampling technique used probability sampling with a simple random sampling, obtaining 86 respondents. The research instrument used a questionnaire on knowledge, family support, and readiness of young women to menarche. Data analysis using the Spearman rho test. The results showed that 53 respondents (61.6%) had moderate knowledge. Family support was in the high category for 69 respondents (80.2%). The readiness of young women in the medium category was 42 respondents (48.8%). There is a relationship between knowledge and readiness of young women (ρ value = 0.001; r = 0.340). There is a relationship between family support and the readiness of young women (ρ value = 0.014; r = 0.264). The implication of this research is that it is hoped that families will increase their support in preparing for menarche. Families and related parties such as schools are expected to provide more education regarding preparation for menarche.